2022
DOI: 10.1007/s10238-022-00864-7
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-33 and soluble suppression of tumorigenicity 2 in scleroderma cardiac involvement

Abstract: Interleukin (IL)-33 is part of the IL-1 family of cytokines and soluble suppression of tumorigenicity 2 (sST2) is part of the family of IL-1 receptors. In systemic sclerosis (SSc), IL-33 and sST2 are involved in cardiac manifestations such as diastolic dysfunction (DD), autonomic dysfunction (AD) and right ventricular–pulmonary arterial coupling assessed by tricuspid annular plane systolic excursion (TAPSE)/systolic pulmonary artery pressure (sPAP). Serum levels of IL33 and sST2 were assessed in 50 SSc patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…72 In systemic sclerosis, an increase in IL-33 and sST2 are associated with the involvement of the heart such as cardiac diastolic dysfunction, and the sST2 exhibited a negative linear correlation with diastolic dysfunction. 73 Another study also revealed increased IL33 and sST2 in systemic sclerosis patients that are associated with microvascular damage. 74 It was reported that serum sST2 and IL-33 were dramatically higher in atrial fibrillation patients than in healthy volunteers.…”
Section: Role Of Il-33 In Cardiac Diseasementioning
confidence: 95%
“…72 In systemic sclerosis, an increase in IL-33 and sST2 are associated with the involvement of the heart such as cardiac diastolic dysfunction, and the sST2 exhibited a negative linear correlation with diastolic dysfunction. 73 Another study also revealed increased IL33 and sST2 in systemic sclerosis patients that are associated with microvascular damage. 74 It was reported that serum sST2 and IL-33 were dramatically higher in atrial fibrillation patients than in healthy volunteers.…”
Section: Role Of Il-33 In Cardiac Diseasementioning
confidence: 95%
“…Circulating IL18 levels were found to be significantly higher in SSc patients respect to controls [ 134 , 135 ] and, interestingly, serum levels of IL18-binding protein isoform a (IL18BPa), a soluble decoy receptor for IL18, were also found to be elevated in SSc circulation and to positively correlate with sPAP [ 136 ]. As far as IL33 is concerned, different studies reported a significant increase in its circulating levels in SSc [ 137 , 138 , 139 , 140 , 141 ], particularly in patients with DUs [ 137 , 141 ]. Notably, circulating values of soluble suppression of tumorigenicity 2 (ST2), a member of the IL1R/Toll-like receptor family that IL33 binds to, were also found to be higher in SSc patients and to correlate with diastolic dysfunction, sPAP, DUs, and NVC abnormalities [ 140 , 141 ].…”
Section: Cytokinesmentioning
confidence: 99%
“…As far as IL33 is concerned, different studies reported a significant increase in its circulating levels in SSc [ 137 , 138 , 139 , 140 , 141 ], particularly in patients with DUs [ 137 , 141 ]. Notably, circulating values of soluble suppression of tumorigenicity 2 (ST2), a member of the IL1R/Toll-like receptor family that IL33 binds to, were also found to be higher in SSc patients and to correlate with diastolic dysfunction, sPAP, DUs, and NVC abnormalities [ 140 , 141 ]. In particular, ST2 was increased in SSc patients with diastolic dysfunction and lower in those with elevated sPAP [ 140 ].…”
Section: Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…BACE1 can also target the IL-1 receptor 2 (IL-1R2) for cleavage, modulating systemic IL-1 activity through soluble IL1R2 release (12). This is interesting as several IL-1 family members including IL-33 have been implicated in SSc (13). Furthermore, BACE1 expression levels are upregulated by NF-κB through binding of the p65 subunit to the BACE1 promoter (14).…”
Section: Introductionmentioning
confidence: 99%